Immunity and Protective Efficacy of Mannose Conjugated Chitosan-Based Influenza Nanovaccine in Maternal Antibody Positive Pigs - Renu, Sankar; Feliciano-Ruiz, Ninoshkaly; Patil, Veerupaxagouda; Schrock, Jennifer; Han, Yi; Ramesh, Anikethana; Dhakal, Santosh; Hanson, Juliette; Krakowka, Steven; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2021)
Parenteral administration of killed/inactivated swine influenza A virus (SwIAV) vaccine in weaned piglets provides variable levels of immunity due to the presence of preexisting virus specific maternal derived antibodies (MDA). To overcome the effect of MDA on SwIAV vaccine in piglets, we developed an intranasal deliverable killed SwIAV antigen (KAg) encapsulated chitosan nanoparticles (CS NPs-KAg) vaccine. Further, to target the candidate vaccine to dendritic cells and macrophages which express mannose receptor, we conjugated mannose to chitosan (mCS) and formulated KAg encapsulated mCS nanoparticles (mCS NPs-KAg) vaccine. In MDA-positive piglets, prime-boost intranasal inoculation of mCS NPs-KAg vaccine elicited enhanced homologous (H1N2-OH10), heterologous (H1N1-OH7), and heterosubtypic (H3N2-OH4) influenza virus-specific secretory IgA (sIgA) antibody response in nasal passage compared to CS NPs-KAg vaccinates. In vaccinated upon challenged with a heterologous SwIAV H1N1, both mCS NPs-KAg and CS NPs-KAg vaccinates augmented H1N2-OH10, H1N1-OH7, and H3N2-OH4 virus-specific sIgA antibody responses in nasal swab, lung lysate, and bronchoalveolar lavage (BAL) fluid; and IgG antibody levels in lung lysate and BAL fluid samples. Whereas the multivalent commercial inactivated SwIAV vaccine delivered intramuscularly increased serum IgG antibody response. In mCS NPs-KAg and CS NPs-KAg vaccinates increased H1N2-OH10 but not H1N1-OH7 and H3N2-OH4-specific serum hemagglutination inhibition titers were observed. Additionally, mCS NPs-KAg vaccine increased specific recall lymphocyte proliferation and cytokines IL-4, IL-10, and IFNγ gene expression compared to CS NPs-KAg and commercial SwIAV vaccinates in tracheobronchial lymph nodes. Consistent with the immune response both mCS NPs-KAg and CS NPs-KAg vaccinates cleared the challenge H1N1-OH7 virus load in upper and lower respiratory tract more efficiently when compared to commercial vaccine. The virus clearance was associated with reduced gross lung lesions. Overall, mCS NP-KAg vaccine intranasal immunization in MDA-positive pigs induced a robust cross-reactive immunity and offered protection against influenza virus.